Rapidly Growing Ovarian Granulosa Cell Tumor Following Complete Debulking for Suspected Ovarian Cancer with Histopathology Result of Benign Ovarian Cyst - Muhammad, Syamel; Antonius, Puja Agung; Oktavian, Rizki; Savannah, Aisha (Molecular and Cellular Biomedical Sciences, 2023)
Ovarian granulosa cell tumor (GCT) is a rare low-grade malignancy condition. One type of GCT is adult GCT (AGCT), which has the tendency for late recurrence. AGCT is clinically palpable and focally cystic and solid. In this case report, a condition of recurrent ovarian cancer after laparotomy debulking surgery was reported. A 57-year-old woman, who was diagnosed with AGCT, had a history of laparotomy debulking three months prior and complained of abdominal pain and enlargement, along with significant weight loss. Ultrasound examination revealed a solid cyst, raising suspicion of recurrent ovarian cancer. Laboratory results indicated elevated CA-125 levels. Histopathology results confirmed metastasis of AGCT, after the second laparotomy debulking was done. Recurrence of GCT is uncommon within three months of debulking. In this rare condition, we suggested a laparotomy debulking and adjuvant chemotherapy as a treatment. Effectiveness of treatment of recurrent disease is an independent risk factor to reduce the risk of another relapse and increase the survival rate.Keywords: granulosa cell tumor, ovarian cancer, debulking